Towards developing high-fidelity simulated learning environment training modules in audiology - Dzulkarnain, Ahmad Aidil Arafat; Rahmat, Sarah; Mohd Puzi, Nur Ain Fathanah; Badzis, Mastura (Malaysian Medical Association, 2017)
Introduction: This discussion paper reviews and synthesises the literature on simulated learning environment (SLE) from allied health sciences, medical and nursing in general and audiology specifically. The focus of the paper is on discussing the use of high-fidelity (HF) SLE and describing the challenges for developing a HF SLE for clinical audiology training. Methods: Through the review of the literature, this paper discusses seven questions, (i) What is SLE? (ii) What are the types of SLEs? (iii) How is SLE classified? (iv) What is HF SLE? (v) What types of SLEs are available in audiology and their level of fidelity? (vi) What are the components needed for developing HF SLE? (vii) What are the possible types of HF SLEs that are suitable for audiology training? Publications were identified by structured searches from three major databases PubMed, Web of Knowledge and PsychInfo and from the reference lists of relevant articles. The authors discussed and mapped the levels of fidelity of SLE audiology training modules from the literature and the learning domains involved in the clinical audiology courses. Results: The discussion paper has highlighted that most of the existing SLE audiology training modules consist of either low- or medium-fidelity types of simulators. Those components needed to achieve a HF SLE for audiology training are also highlighted. Conclusion: Overall, this review recommends that the combined approach of different levels and types of SLE could be used to obtain a HF SLE training module in audiology training.